The Impact of Technology-Based Teaching Methods on English Speaking Skills in Rural Secondary Schools - Merlin Helentina Napitupulu; Maria Wilhelmina Wisrance; Thresia Trivict Semiun (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study investigates the impact of technology-based teaching methods on students’ English-speaking skills in secondary schools in rural Indonesia. Using a quasi-experimental design with control and experimental groups for six weeks, the research involved 70 students from two secondary schools in Kefamenanu, East Nusa Tenggara. One group received instruction using traditional methods, while the other, the experimental group received instruction through digital tools—Flipgrid, Google Meet, and multimedia apps—while the control group followed traditional methods. Data were collected using pre-tests and post-tests focused on fluency, pronunciation, vocabulary, and coherence; student questionnaires; and classroom observations. Findings reveal that students in the experimental group outperformed their peers, with a statistically significant gain of 13.5 points in speaking scores (p < 0.001, Cohen’s d = 2.10), compared to 4.4 points in the control group. The findings reveal a significant improvement in the speaking abilities of students exposed to technology-based instruction compared to those taught through conventional means. Students in the experimental group demonstrated higher levels of confidence, engagement, and linguistic accuracy during speaking tasks. The study underscores the pedagogical value of incorporating digital tools to foster more interactive and learner-centered classroom environments. It further suggests that, when thoughtfully integrated, technology can effectively support the development of communicative competence in English as a Foreign Language (EFL) setting. This research contributes to the growing discourse on educational technology in language learning and offers practical implications for English educators, curriculum developers, and policymakers seeking to improve speaking outcomes in secondary education.